2019
DOI: 10.1038/s41598-019-41381-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube incorporation in PMMA to prevent microbial adhesion

Abstract: Although PMMA-based biomaterials are widely used in clinics, a major hurdle, namely, their poor antimicrobial (i.e., adhesion) properties, remains and can accelerate infections. In this study, carboxylated multiwalled carbon nanotubes (CNTs) were incorporated into poly(methyl methacrylate) (PMMA) to achieve drug-free antimicrobial adhesion properties. After characterizing the mechanical/surface properties, the anti-adhesive effects against 3 different oral microbial species (Staphylococcus aureus, Streptococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 55 publications
3
43
0
2
Order By: Relevance
“…Hashem, et al 40 (2017) suggested that the addition of titanium oxide nanoparticles to PMMA improves its wettability. However, Kim, et al 41 (2019) found an increase in the water contact angle with increasing carbon nanotube content in PMMA. Their study demonstrated that an increase in the contact angle increases the material's surface hydrophobicity, enhancing Candida albicans adhesion 42 .…”
Section: Discussionmentioning
confidence: 98%
“…Hashem, et al 40 (2017) suggested that the addition of titanium oxide nanoparticles to PMMA improves its wettability. However, Kim, et al 41 (2019) found an increase in the water contact angle with increasing carbon nanotube content in PMMA. Their study demonstrated that an increase in the contact angle increases the material's surface hydrophobicity, enhancing Candida albicans adhesion 42 .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Kim et al [16] used carbon nanotubes (CNT) (0.25/2 wt%) as an additive in PMMA finding a reduction of C. albicans , S. aureus, and S. mutans adhesions of 35–95%. However, there are many concerns about the use of CNTs for clinical purposes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides play a vital role in agricultural production, however, which not only causes serious environmental pollution, but also becomes a great harm to human health. [41][42][43] Effective detection of pesticides in the environment is needed and CPs-based sensors provided a viable alternative technique. We tried to detect pesticides in water with CP 2 as a uorescent probe which exhibited good performance in antibiotics recognition.…”
Section: Detection Of Pesticidesmentioning
confidence: 99%